2020
DOI: 10.1016/j.sleepx.2020.100022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of supplemental melatonin for delayed sleep–wake phase disorder in children: an overview

Abstract: Delayed sleep–wake phase disorder (DSPD) is the most frequently occurring intrinsic circadian rhythm sleep–wake disorder, with the highest prevalence in adolescence. Melatonin is the first-choice drug treatment. However, to date melatonin (in a controlled-release formulation) is only authorised for the treatment of insomnia in children with autism or Smiths-Magenis syndrome. Concerns have been raised with respect to the safety and efficacy of melatonin for more general use in children, as melatonin has not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 158 publications
0
12
0
Order By: Relevance
“…This variability could be due to differing or overlapping etiologies of ADHD, whether it is a manifestation of genetic SNPs related to sleep disturbance and circadian rhythm dysfunction or attributed to the melatonin-signaling deficiency. More research is needed to determine appropriate dosage protocols specific to the pathophysiology of ADHD under the supervision of a qualified healthcare professional [ 114 , 115 ].…”
Section: Clinical Usesmentioning
confidence: 99%
“…This variability could be due to differing or overlapping etiologies of ADHD, whether it is a manifestation of genetic SNPs related to sleep disturbance and circadian rhythm dysfunction or attributed to the melatonin-signaling deficiency. More research is needed to determine appropriate dosage protocols specific to the pathophysiology of ADHD under the supervision of a qualified healthcare professional [ 114 , 115 ].…”
Section: Clinical Usesmentioning
confidence: 99%
“…Most of the rest of the evidence regarding melatonin and the potential cellular effects comes from our understanding of melatonin supplementation and these relationships with circadian rhythms and sleep [57,58]. Of particular interest has been the effects of melatonin on children and adolescents, who may be treated with melatonin for sleepwake and sleep phase disorders that have recently been observed at increasingly higher rates [59,60]. Research that seeks to understand the effects of melatonin and how normal oral cells and tissues function in response to melatonin without injury or insult is therefore of increasing importance [61].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 19 randomized controlled trials of IR melatonin daily treatment on a total of 841 children and adolescents with DSPD showed a consistent improvement of sleep latency by 22 to 60 min without serious adverse effects. 47 A meta-analysis of seven RCTs assessing efficacy and safety of melatonin in 387 children and adolescents with sleep-onset insomnia associated with DSPD from 6 to 19 years old concluded that melatonin advanced mean sleep-onset time by 37 min and DLMO by 49 min, 46 including two RCTS on children and adolescents with ADHD (see Table 1 ). 134 , 135 Another study from Mohammadi et al in 2012 evaluated the effect of combined treatment of melatonin (3–6 mg) and methylphenidate (1 mg/kg) in a group of 26 children with ADHD whose sleep symptoms were assessed using the Sleep Disturbance Scale for Children (SDSC) parent-questionnaire, with a placebo group of 24 children treated with placebo+methylphenidate (1 mg/kg).…”
Section: Part II Melatonin As An Etiological Treatment In Pediatric I...mentioning
confidence: 99%
“…Alternatively, for a combination of the chronobiotic, chronohypnotic and soporific effect of IR melatonin (see Part I, above), a prescription of 1 to 3 mg at bedtime is equally interesting (though the degree of the induced phase shift will be less than if given several hours earlier, see Figure 2 ). 47 , 132 Even though the benign safety profile of melatonin is established (see above), as chronotype varies across lifespan and endogenous circadian rhythm may change during long-term treatment, it is recommended to stop and reassess the indication of melatonin treatment regularly (at least once a year, for example during the summer holidays).…”
Section: Part II Melatonin As An Etiological Treatment In Pediatric I...mentioning
confidence: 99%
See 1 more Smart Citation